Purity of Islamic Bank: Literature Review - Maya Permata Sari; Mega Dwi Septivani; Rifdatul Husna (International ABEC, 2022)
Islamic banking is one of the fastest-growing industries in the world today. The purpose of this research is to find out the implementation of syariah law in Islamic banking based on previous research. Syariah law is the policy that Islamic banks must follow in their operation and value. It can be an alternative for Muslim population to avoid riba or usury in their financial activity. Many scholars have been finding that Islamic banking is not pure using syariah law. They just clone the products, systems, and even working culture from conventional banks. Our literature review found that most Islamic banking is still trapped in the wrong environment and their human resource did not get adequate knowledge about syariah.